IJTIMOIY TA’MINOTNI MOLIYALASHTIRISH INSTITUTLARINING SAMARADORLIGINI OSHIRISH (Marketing Journal, 2026)
AbstractIn the article is discussed the current social welfare financing mechanisms in theRepublic of Uzbekistan, their effectiveness, and areas for improving theireffectiveness. There is analyzed government strategies, institutional changes, andscientific approaches to improving financial support for social welfare. Attention ispaid to the analysis of funding sources, digitalization of systems, and theimplementation of international experience.Keywords: social security, efficiency, social security financing, digitalization.